Wind Corrections in Flight Path Planning. (16th May 2013) - Selecký, Martin; Váňa, Petr; Rollo, Milan; Meiser, Tomáš
Abstract When operating autonomous unmanned aerial vehicles (UAVs) in real environments it is necessary to deal with the effects of wind that causes the aircraft to drift in a certain direction. In such conditions it is hard or even impossible for UAVs with a bounded turning rate to follow certain trajectories. We designed a method based on an Accelerated A * algorithm that allows the trajectory planner to take the wind effects into account and to generate states that are reachable by UAV. This method was tested on hardware UAV and the reachability of its generated trajectories was compared to the trajectories computed by the original Accelerated A * .